Efficacy of Individual Placement and Support (IPS) on Employment, Education, and Training in Young Adults With Early Psychosis—A Randomized Controlled Trial - Dorothea Jäckel; Andreas Bechdolf; Eva Burkhardt; Michèle Kallenbach; Marie‐Luise Gamig; Anna Mößnang; Karolina Leopold (Brain and Behavior)
ABSTRACT Objective To explore the efficiency of IPS on employment, education, and training (EET) outcomes in young adults with early psychosis. Methods Monocenter parallel arm, randomized controlled trial. Intervention Individual placement and support (IPS) according to the IPS‐Y Fidelity Scale with an add‐on of up to eight sessions of adherence therapy. Main outcome measures EET at least 15 h per week for at least 1 week in the follow‐up. Secondary outcomes included EET rates, duration in EET, and total wages. Additionally, subsample analyses were carried out. Results A total of 94 young adults (18–35 years) with early psychosis in an outpatient psychiatric service were randomly assigned to 12‐month IPS according to program fidelity and standard care versus standard care alone. Four patients were excluded from the analysis because of early dropout after baseline, leaving 90 participants—46 in the IPS group and 44 in the TAU group—for intention to treat (ITT) analysis. EET rate for at least 15 h per week was significantly higher in the IPS group, 78% (36/46) versus 55% (24/44) in the TAU group. The percentage of participants in EET for at least 1 week in the follow‐up was 83% (38/46) versus 59% (26/44). The number of weeks in EET was significantly higher in the IPS group (mean = 31.5 weeks, SD = 20.5 versus mean = 18.4 weeks, SD = 21.2), and the total wages were higher in favor of the IPS group (mean = €10,242, SD = 13,437 versus mean = €5217, SE = 7871). Conclusion IPS integrated into outpatient psychiatric services improves EET in young adults with early psychosis in Germany.